Addressing crises of order: judicial state-building in the wake of conflict - Swenson, G (2015)
Promoting the rule of law is vital for the success of domestic and international postconflict state-building efforts. Yet in post-conflict settings, non-state justice systems handle most disputes, retaining substantial autonomy and authority. Legal pluralism's importance, however, is rarely recognized and dramatically under-theorized. This thesis demonstrates that multiple justice systems can co-exist and contribute to the development of a democratic state bound by the rule of law. Domestic and international efforts, however, must be cognizant of the overarching legal pluralism paradigm that exists when trying to build the rule of law and tailor their strategies accordingly. By drawing on two divergent case studies, Timor-Leste and Afghanistan, this dissertation examines the conditions under which the rule of law can be advanced in post-conflict settings featuring a high degree of legal pluralism and substantial international involvement. Four distinct legal pluralism paradigms are proposed – combative, competitive, cooperative, and benign – in order to understand how legal pluralism functions in practice. Timor-Leste successfully advanced the rule of law because the major parties remained committed to democracy and developed institutions promoting accountability, inclusivity, and legality. The state meaningfully collaborated with key non-state actors. While the process was imperfect, Timorese state-officials effectively mediated between the international community and local-level figures. This contributed to the effective transformation of a competitive legal pluralist environment into a cooperative one. The international community largely reinforced these positive trends. Conversely, Afghanistan's post-2001 regime squandered the opportunity to build a democratic state bound by the rule of law. Simultaneously, it failed to mediate between the international community and the tribal and religious authorities essential for legitimate rule. Despite international actor's substantial influence, external aid did little good and was often counter-productive. These divergent approaches helps explain judicial state-building's failure and the corresponding slide from competitive into combative legal pluralism against the Taliban.